Micellar Nanoformulation of Berberine to Mitigate Doxorubicin-induced Cardiotoxicity: A Cell-line Study - Noora Alyasari; Anwar Almzaiel (Al-Anbar Medical Journal)
Background: Doxorubicin-induced cardiotoxicity (DIC) is a major complication of cancer chemotherapy. Thus, developing effective myocardial protection strategies during doxorubicin (Dox) therapy is a medical necessity.Objectives: To evaluate and compare the cardioprotective effectiveness of free berberine (Ber) and berberine loaded in micelles (mBer) against DIC.Materials and Methods: The study, which was conducted in 2023, employed the H9c2 cell line, derived from embryonic cardiomyocytes, as a model. The study included a control group and six experimental groups: the Ber-treated group, the mBer-treated group, the Dox-treated group, the Ber-Dox combination-treated group, and the mBer-Dox combination-treated group, as well as the void micelles-treated group. The study evaluated the alterations in several cardiotoxicity markers with triplicate measurements: [lactate dehydrogenase (LDH), creatine kinase myocardial band (CK-MB), and cardiac troponin I (cTn-1)], lipid peroxidation indicator (malondialdehyde (MDA), oxidative stress markers [Reduced glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD), inflammatory cytokines (interleukin-1β (IL-1β) and interleukin-6 (IL-6)], and the activity of the apoptosis proteins caspases 3/7. Results: The DOX group demonstrated significant increases in cardiotoxicity enzyme indices, lipid peroxidation, generation of free radicals, inflammatory cytokines, and caspase 3/7 activity relative to the control group. When Ber, or mBer, was co-delivered with Dox, the levels of LDH, CK-MB, cTn-1, and MDA significantly decreased. Whereas the activities of SOD and CAT were significantly improved when Ber, or mBer, was co-delivered with Dox. They reduced the elevation in both IL- β and IL-6 levels as well as the activities of caspases 3 and 7 induced by Dox. Importantly, the utilization of the micellar formulation of Ber in conjunction with Dox significantly enhanced the cardioprotective efficacy of Ber against DIC in H9c2 cells. Conclusion: Our results suggest that mBer offers a novel Ber delivery approach and prospective therapeutic strategy for the treatment of DIC.